(untitled) (Nigerian Journal of Technology, 2020)
The project involved the design and construction of a three-blade wind turbine, selection of generator by consideration of the available wind speed and the maximum generated voltage per revolution, and assembly of the pulse width modulated inverter with microontroller based status display and low battery shutdown system. On completion of the work, tests were conducted and the result shows that the design work was very good, the output of the generator was good enough to charge the batteries and the inverter performed an excellent task of converting the direct current (DC) voltage available in the battery to alternating current (AC) at 230V 50Hz 20”. Furthermore, results from the discharge characteristics of the battery shows that as the battery is being used up, the output voltage remains constant. http://dx.doi.org/10.4314/njt.v39i2.17